The Apalachicola Barrier Island complex: a benchmark for MIS 5e (125 ka) sea-level oscillations? - Nikos Georgiou; Alexander R. Simms; Roger C. Creel; Silas Dean; Denovan Chauveau; Ciro Cerrone; Claudia Caporizzo; Alessio Rovere (Geomorphology, 2026)

Fast landslide events in calcareous debris and weathered pyroclastic soils: a case study in Southern Italy - L. Massaro; C. Cerrone; M. De Falco; E. Marino; M. Pirone; N. Santangelo; A. Santo (Bulletin of Engineering Geology and the Environment, 2026)
In this study, we analyse the occurrence of fast landslides developed in detrital limestone-dolomitic deposits and colluvium deposits on steep dolomitic slopes in Southern Italy. In the past few decades, the literature research on this type of landslide has mainly focussed on events developed in pyroclastic soils. However, the results of this study show that, even in weathered calcareous debris and with moderate deposit thickness (0.5–2 m), these phenomena can evolve into dangerous events. In the investigated area, the debris slides were mapped, providing a complete dataset of events that occurred in the 2022–2023 period. Successively, field and drone surveys enabled defining the stratigraphy of the involved deposits, the estimation of the mobilised volumes, and sampling for a preliminary lab-based geotechnical characterisation. Moreover, the rainfall data were acquired to identify their relationship with the landslide events. The results showed that the debris slides in the area involve cover deposits of moderate thickness (0.5–2 m) on slopes dipping from 27° to 45°. Most of the events developed a sliding surface at the interface between an ancient paleosoil and the detrital and colluvial deposits, mobilising downstream with significant runout and increasing volumes. Critical rainfall events, exceeding 100 mm daily, combined with antecedent periods of intense rainfalls, acted as key triggers for these landslides. This work provides valuable insights for land-use planning and risk mitigation strategies, particularly in the context of increasing rainfall due to global warming.

Last interglacial relative sea-level changes at Myrtle Beach, South Carolina - S. Dean; N. Georgiou; R. Poirier; W.R. Doar; D. Brill; D. Chauveau; C. Cerrone; J. Austermann; A. Rovere (Quaternary Science Reviews, 2026)

The last interglacial transgression in Italy: the breath of the Italian coasts documented by 461 sites - F. Antonioli; L. Ferranti; M. Agate; A. Ascione; C. Cerrone; V. De Santis; G. Deiana; A. Fontana; S. Furlani; G. Leoni; V. Lo Presti; L. Guerrieri; et al. (Quaternary Science Reviews, 2025)

Correcting physics-based global tide and storm water level forecasts with the temporal fusion transformer - A.R. Cerrone; L.G. Westerink; G. Ling; C.P. Blakely; D. Wirasaet; C. Dawson; J.J. Westerink (Ocean Modelling, 2025)

Pseudomonas umsongensis GO16 as a platform for the in vivo synthesis of short and medium chain length polyhydroxyalkanoate blends - Federico Cerrone; Binbin Zhou; Agathe Mouren; Luc Avérous; Stephen Conroy; Jeremy C. Simpson; Kevin E. O'Connor; Tanja Narancic (Bioresource Technology, 2023)

β-Adrenergic receptor stimulation induces endoplasmic reticulum stress in adult cardiac myocytes: role in apoptosis - Suman Dalal; Cerrone R. Foster; Bhudev C. Das; Mahipal Singh; Krishna Singh (Molecular and Cellular Biochemistry, 2012)